Agronomical performances of doubled haploids derived through androgenesis of a quality rice hybrid 27P63 - Pattnaik, Snigdha Samir; Rout, Prachitara; Bhuyan, Sudhansu Sekhar; Dash, Byomkesh; Verma, Ram Lakhan; C, Parmeswarn; Katara, Jawahar Lal; S, Sabarinathan; Nayak, Baijayanti; Ramesh, Narayanperumala; Samantaray, Sanghamitra (ORYZA-An International Journal of Rice, 2023)
Utilisation of the doubled haploid method presents a promising opportunity to achieve homozygosity in an efficient manner. The present study centred on the identification of potential doubled haploids for the assessment of various agronomic traits, including days to 50% flowering, plant height, number of tillers, panicle length, and grain yield across three distinct growing seasons. The results of the analysis of variance indicated that there were no statistically significant differences within the DHs, indicating homogeneity. However, there was a significant amount of variation observed between the DHs.The present study reports on various traits, including panicle length and number of tillers, which exhibited a coefficient of variation of 18.02% and 16.81%, respectively. Additionally, grain yield, plant height, and days to 50% flowering displayed a coefficient of variation of 20.06%, 18.40%, and 18.72%, respectively. In general, among the 21 DHs evaluated, 6 DHs displayed superior yield while 2 DHs demonstrated comparable yield to the parent hybrid across 3 consecutive seasons. DHs possessing potential yield traits have the potential to enhance rice productivity through their utilisation in breeding initiatives.